Stock Price Determinants in Defensive Industries: The Role of Macroeconomic Factors and Profit Growth in Indonesia’s Pharmaceutical Sector - Ellyn Octavianty; Agung Fajar Ilmiyono; Nilda Tartilla; Davina Dwi Andriani (Institut Bisnis dan Informatika Kesatuan, 2025)
Stock price fluctuations are shaped by both macroeconomic conditions and firm-level performance, making them a central focus in capital market research. The pharmaceutical sector, as part of the consumer goods industry, is often classified as a defensive sector where demand remains relatively stable during economic uncertainty. This study examines the effect of inflation, interest rates, and profit growth on the stock prices of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2020. Using purposive sampling of eight firms and multiple linear regression analysis, the results show that the three variables have no significant impact on stock prices, either individually or collectively. The findings contribute theoretically by clarifying the limited relevance of traditional macroeconomic indicators in defensive industries, suggesting that sectoral and firm-specific factors may play a more dominant role. Practically, the study advises investors to focus on regulatory frameworks, product innovation, and public health dynamics when evaluating pharmaceutical equities. From a policy perspective, the results imply that conventional monetary instruments exert limited direct influence on defensive industries, highlighting the need for sector-specific policies to sustain investor confidence and industry growth. Keywords: Inflation, Interest Rates, Profit Growth, Stock Prices, Pharmaceutical Sector